2018
DOI: 10.1063/1.5033991
|View full text |Cite
|
Sign up to set email alerts
|

Efficient injection of radiation-pressure-accelerated sub-relativistic protons into laser wakefield acceleration based on 10 PW lasers

Abstract: 1We propose a hybrid laser-driven ion acceleration scheme using a combination target of a solid foil and a density-tailored background plasma. In the first stage, a sub-relativistic proton beam can be generated by the radiation pressure acceleration in the intense laser interaction with the solid foil. In the second stage, this sub-relativistic proton beam is further accelerated by the laser wakefield driven by the same laser pulse in a near-critical-density background plasma with a decreasing density profile.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 49 publications
0
7
0
Order By: Relevance
“…p /c 2 ) 1/2 can be deduced from dγ p /dx ≈ πa 0 m e /λm p [26]. For a 0 = 100 and v p 0.73c (the corresponding E p 500 MeV) obtained in the laser-foil interaction stage, the sub-relativistic protons will be accelerated rapidly to relativistic speed in tens of microns.…”
Section: Theory and Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…p /c 2 ) 1/2 can be deduced from dγ p /dx ≈ πa 0 m e /λm p [26]. For a 0 = 100 and v p 0.73c (the corresponding E p 500 MeV) obtained in the laser-foil interaction stage, the sub-relativistic protons will be accelerated rapidly to relativistic speed in tens of microns.…”
Section: Theory and Analysismentioning
confidence: 99%
“…To achieve quasi-monoenergetic ion beams, several mechanisms have been investigated, such as collisionless shock acceleration (CSA) [16][17][18][19][20], radiation pressure acceleration (RPA) [21][22][23][24][25], and RPA-wakefiled hybrid acceleration [26]. In one of the most-investigated mechanisms, light-sail mode of RPA, the acceleration of ions to ultrahigh energies is allowed, where a nanoscale solid foil could be continuously accelerated by an ultrashort, ultraintense laser pulse under the ideal conditions [21,22,27].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the protons need to be preaccelerated to a sufficient energy in order to be injected into the wakefield. In the work of Liu et al it was shown that protons preaccelerated by the radiation pressure acceleration in a thin solid foil could be captured by the LWFA in an underdense gas [23].…”
Section: Introductionmentioning
confidence: 99%
“…Besides, the protons need to be pre-accelerated to a sufficient energy in order to be injected into the wakefield. In the research of M. Liu et al, with pre-accelerated by the radiation pressure acceleration (RPA) in a thin solid foil, the protons were captured by the LWFA in an underdense gas [23].…”
Section: Introductionmentioning
confidence: 99%